1998
DOI: 10.1111/1467-9450.00064
|View full text |Cite
|
Sign up to set email alerts
|

Social attitudes and education: Self‐selection or socialization?

Abstract: The aim of this study was to replicate earlier findings (Ekehammar et al., 1987) concerning the relationship between social attitudes and educational direction and field of study, by addressing further the causality issue. The sample comprised 256 Swedish adolescents from metropolitan Stockholm attending the two lowest grades in secondary school (modal age was 17 years). The main findings of the previous study were replicated, although the statistical power was weaker. Two higher-order attitude dimensions (lab… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2002
2002
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 16 publications
0
6
0
Order By: Relevance
“…One can make the argument that the addition of the SES variables dilutes the effects for parental involvement not because the causal nature of SES so much, as the fact that there are other causal components beyond SES and parental involvement that influence both variables. In terms of SES specifically, a growing number of studies indicate that the level of SES can be a result of various other factors rather than a primary cause (Gortmaker, Steven, Must, Perrin, & Sobol, 1993;Jeynes, 1998;Zakrisson & Ekehammer, 1998). Crane (1996) demonstrated that the influence of SES as a causal variable can be overestimated if mediating family factors are not taken into account.…”
Section: Research Question 3: Specific Components Of Parental Involvementmentioning
confidence: 99%
“…One can make the argument that the addition of the SES variables dilutes the effects for parental involvement not because the causal nature of SES so much, as the fact that there are other causal components beyond SES and parental involvement that influence both variables. In terms of SES specifically, a growing number of studies indicate that the level of SES can be a result of various other factors rather than a primary cause (Gortmaker, Steven, Must, Perrin, & Sobol, 1993;Jeynes, 1998;Zakrisson & Ekehammer, 1998). Crane (1996) demonstrated that the influence of SES as a causal variable can be overestimated if mediating family factors are not taken into account.…”
Section: Research Question 3: Specific Components Of Parental Involvementmentioning
confidence: 99%
“…Choosing a subject to study (self-selection), be it sciences, engineering, business, culture or social relations, is associated with cognitive orientations, values and norms. Students enrolling in different subjects differ regarding career expectations, cognitive abilities, preferred lifestyle and with respect to their attitude towards science (Zarkisson and Ekehammar 1998). This attitude evolves and may vary over time: During their studies, students do not only acquire specialized knowledge but are also exposed to the standards, supervision and peer culture of their disciplines amongst which are considerable differences (Weidman et al 2001).…”
Section: Academic Discipline (Vocational and Career Choice)mentioning
confidence: 99%
“…Based on this description, the research questions include the following points: (1) what the current research trend on learning social attitudes is? (2) what are future implications for learning social attitudes due to the existing research's objectives and limitations?…”
Section: Purpose Of the Studymentioning
confidence: 99%
“…Therefore, education is considered a very appropriate socialization agent about attitudes and behaviour as social class indicators. Also, education is empirically proven to have a liberalizing effect on social attitudes that are not related to non-economic problems [2]. Thus, social attitudes have a significant role to be developed for students in their educational environment.…”
Section: Introductionmentioning
confidence: 99%